Online Food Delivery Application - Yuni Nur Aini; Martha Dwi Mulyanti; M. Wahyuli Setiawan; Yopi Yudha Utama (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study aims to review how effective the online food delivery application is that is used to optimize MSME income in the culinary field, especially at Seblak Incezz Rejomulyo, Kediri City. Design/methodology/approach: This is a qualitative study that employs an analytical descriptive approach. The analytical-descriptive approach was chosen because it provides an explanation or elaboration regarding variable objects obtained from the data that has been collected. Findings: The use of online food delivery services is effective in optimizing sales volume at Seblak Incezz Rejomulyo, Kediri City. In the end, the more sales increase, the entity's income will also increase. Research limitations/implications: Only focus on one sector of SMEs, so the results cannot be compared with SMEs in other fields. Practical implications: This research shows that MSMEs need to adapt according to technological developments. This will eventually have an effect on the sustainability of MSMEs because it can increase sales and income for MSMEs. Originality/value: Seblak Incezz is one of the MSMEs in the culinary field in the city of Kediri, which is growing from year to year. Paper type: Research Paper